Local Wisdom of the Fisherman Community of Muara-Binuageun in Lebak Regency Regarding Disaster Mitigation and Preparedness - Rian Fauzi; Samsu Bahri (Department of Tadris IPS FITK IAIN Syekh Nurjati Cirebon, 2022)
Abstract: The citizen of Muara Binuangeun, the traditions of their ancestors must be maintained. In this case local wisdom is a human effort by using his mind to act and behave towards something, object or event that occurs in a certain space and Mitigation is an effort to reduce disaster risk, in this case to save people's lives the need to understand local wisdom have in disaster prevention or actions to reduce disasters. This study uses a qualitative method. Conducting observations for initial research studies and interviewing informants as well as deepening research supporting documents. Analysis of checking the validity of the data in this study used qualitative data analysis. The research results obtained (1) Mitigation is very important for people living in disaster-prone areas. Mitigation based on natural knowledge based on experience makes it a reference in people's lives. Local wisdom that is owned by the community is able to make a cultural wealth that grows and develops in society. (2) the fishermen community of Muara-Binuagen applies local wisdom in the form of hereditary knowledge which is told through bedtime stories from parents' experiences in dealing with various disasters that have been experienced by seeing natural signs in the form of symptoms. (3) In the Muara-binageun area there are several people who are of different ethnic groups but have good relations, protecting and caring for each other is their good habit, Muara-Binuageun is a disaster-prone area so in this case the community works together in preparing themselves if one day an unexpected disaster occurs.Keywords: Local wisdom, Mitigation, Disaster Preparedness, and Fishermen of Muara-Binuageun. Abstrak: Bagi masyarakat Binuangeun tradisi nenek moyang merupakan hal yang harus di pertahankan. Dalam hal ini kearifan lokal adalah usaha manusia dengan menggunakan akal budinya untuk bertindak dan bersikap terhadap sesuatu, objek, atau peristiwa yang terjadi dalam ruang tertentu dan Mitigasi merupakan upaya untuk mengurangi resiko bencana, dalam hal ini untuk menyelamatkan kehidupan masyarakat perlunya memahami kearifan lokal yang di miliki dalam pencegahan bencana ataupun tindakan untuk mengurangi bencana. Penelitian ini menggunakan metode kualitatif. Melakukan observasi untuk studi awal penelitian dan wawancara narasumber serta pendalaman dokumen penunjang penelitian. Analisis pemeriksaan keabsahan data pada penelitian ini menggunakan analisis data kualitatif. Adapun Hasil penelitian yang didapatkan (1) Mitigasi merupakan hal yang sangat penting bagi masyarakat yang tinggal di daerah rawan Bencana. Mitigasi yang bersumber pada pengetahuan alam yang berdasarkan pengalaman menjadikan sebuah acuan dalam kehidupan masyarakat. Kearifan lokal yang di miliki masyarakat mampu menjadikan sebuah kekayaan budaya yang tumbuh dan berkembang dalam masyarakat. (2) masyarakat Nelayan Muara-Binuagen menerapkan kearifan lokal berupa pengetahuan turun-temurun yang diceritakan melalui dongeng penghantar tidur dari pengalaman orangtua dalam mengahadapi berbagai bencana yang telah di alami dengan melihat tanda-tanda alam berupa gejala. (3) Di daerah Muara-binageun terdapat beberapa masyarakat yang berbeda suku akan tetapi memiliki hubungan yang baik, saling melindungi dan saling peduli merupakan kebiasaan baik mereka, Muara-Binuageun merupakan wilayah yang rawan bencana sehingga dalam hal ini masyarakat bekerja sama dalam menyiapkan diri mereka jika suatu saat terjadi bencana yang tak diharapkan. Kata Kunci: Kearifan lokal , Mitigasi, Kesiagaan Bencana, dan Nelayan Muara-Binuageun.